Intravascular Stem Cell Bioreactor for Prevention of Adverse Remodeling After Myocardial Infarction. Issue 15 (6th August 2019) - Johnston, Peter V.; Hwang, Chao‐Wei; Bogdan, Virginia; Mills, Kevin J.; Eggan, Elliott R.; Leszczynska, Aleksandra; Wu, Katherine C.; Herzka, Daniel A.; Brinker, Jeffrey A.; Schulman, Steven P.; Banerjee, Monisha; Florea, Victoria; et al.
Abstract : Background: Prevention of adverse remodeling after myocardial infarction (MI) is an important goal of stem cell therapy. Clinical trial results vary, however, and poor cell retention and survival after delivery likely limit the opportunity to exert beneficial effects. To overcome these limitations, we built an implantable intravascular bioreactor (IBR) designed to protect contained cells from washout, dilution, and immune attack while allowing sustained release of beneficial paracrine factors. Methods and Results: IBRs were constructed using semipermeable membrane adhered to a clinical‐grade catheter shaft. Mesenchymal stem cell (MSC) viability in and paracrine factor release from IBRs were assessed in vitro and IBR biocompatibility and immune protection confirmed in vivo. In a porcine anterior MI model, IBRs containing 25 million allogeneic MSCs (IBR‐MSCs) were compared with IBRs containing media alone (IBR‐Placebo; n=8 per group) with adverse remodeling assessed by magnetic resonance imaging. Four weeks after MI, IBR‐MSCs had no significant change in end‐diastolic volume (+0.33±4.32 mL; P =0.89), end‐systolic volume (+2.14±4.13 mL; P =0.21), and left ventricular ejection fraction (−2.27±2.94; P =0.33) while IBR‐Placebo had significant increases in end‐diastolic volume (+10.37±3.84 mL; P =0.01) and ESV (+11.35±2.88 mL; P =0.01), and a significant decrease in left ventricular ejection fraction (−5.78±1.70; P =0.025). Eight weeks after MI, adherent pericarditis was present in 0 of 8 IBR‐MSCs versus 4 of 8 IBR‐Placebo ( P =0.02), suggesting an anti‐inflammatory effect. In a separate study, 25 million allogeneic pig MSCs directly injected in the peri‐infarct zone 3 days after MI (n=6) showed no significant benefit in adverse remodeling at 4 weeks compared with IBR‐MSCs. Conclusions: MSCs deployed inside an implantable, removable, and potentially rechargeable bioreactor in a large animal model remain viable, are immunoprotected, and attenuate adverse remodeling 4 weeks after MI.